Molecular phylogeny of the Microsporidia: ecological, ultrastructural and taxonomic considerations - Vossbrinck, Charles R; Debrunner-Vossbrinck, Bettina A (Folia parasitologica, 2005)
The Microsporidia are a group of obligate intracellular parasites, now thought to be derived fungi. Presented here is a comparative small subunit rDNA (ssrDNA) analysis of 125 species of Microsporidia (sequences obtained from GenBank). This analysis shows that groups or clades are formed based largely on habitat and host. This result is supported by comparative molecular analyses of the past decade, and indicates that structural and ultrastructural characters are unreliable for distinguishing among higher-level microsporidian taxa. Our findings indicate the presence of five major clades of Microsporidia which group according to habitat. We present three new classes of Microsporidia based on natural phylogenetic groupings as illustrated by the ssrDNA analysis: Aquasporidia, Marinosporidia and Terresporidia. The names of the proposed classes reflect the habitat of each group. The class Aquasporidia, found primarily in freshwater habitats, is a paraphyletic group consisting of three clades. The Marinosporidia are found in hosts of marine origin and the Terresporidia are primarily from terrestrial environments.
Keywords: databáze nukleových kyselin; Environment; Animals; Databases, Nucleic Acid; životní prostředí; Phylogeny; RNA, Ribosomal; shluková analýza; RNA ribozomální; zvířata; Cluster Analysis; fylogeneze; Microsporidia